Neuropsychodynamic Psychiatry (Springer International Publishing, 2018)
This book presents a comprehensive neuropsychodynamic strategy for treating psychiatric disorders. Rather than pursuing an exclusively biological, psychological, or psychodynamic approach, it offers a methodology that links all three aspects in a unifying, integrative model. Central to this approach is the view of the brain as a bio-psychosocial organ in a neuro-ecological model, rather than the purely neuronal model often presupposed in current neuroscience and psychiatry. Moreover, the book views psychopathological symptoms as spatiotemporal disorders of the altered spatiotemporal structure spanning the brain and its surrounding world. The relation between one of the core symptoms and altered neuronal activity calls for the development of integrated, circular neuropsychodynamic models of psychopathological symptoms in severe psychiatric disorders and their treatment.